Actual diffusivities and diffusion paths of water vapor in asphalt mixtures. (20th May 2019) - Luo, Rong; Tu, Chongzhi
Highlights: Measured water vapor diffusivities in aggregates covered by an asphalt binder. Determined water vapor diffusivities in air voids in asphalt mixtures. Proved actual vapor diffusion in mixture was transitional diffusion in air voids. Demonstrated tortuous paths of actual water vapor diffusion in asphalt mixtures. Abstract: Laboratory experiments have been conducted to measure diffusion parameters following standard test methods. However, these diffusion parameters, while effective measures of asphalt mixtures, were not able to provide the detailed picture of water vapor movement inside the asphalt mixtures. This study investigated the actual diffusivities and diffusion paths of water vapor in typical asphalt mixtures. Water vapor diffusion tests were conducted on aggregates covered by an asphalt binder, and the water vapor diffusivities were determined to be of the order of magnitude of 1 (in the unit of mm 2 /h). Meanwhile, water vapor diffusion in the air voids of typical asphalt mixtures were found to be transitional diffusions based on the estimated average radii of air voids of the mixtures, and the corresponding diffusivities were determined to be of the order of magnitude of 4 (in the unit of mm 2 /h). It was demonstrated that the actual diffusivities of water vapor in asphalt mixtures were the transitional diffusivities in the air voids, the actual diffusion paths were tortuous curves, and the actual diffusion areas were only in the areas of the air voids at the cross sections of the asphalt mixtures. The effective diffusivities of the same asphalt mixtures measured using the standard test method specified in specifications were two orders of magnitude smaller than the actual diffusivities. The tortuosity factors were determined and demonstrated that the actual diffusion paths were more than 10 times longer than the thicknesses of the asphalt mixtures. These findings revealed the complex internal structures of the asphalt mixtures and suggested nonuniform water molecule distributions inside the asphalt mixtures.